Identifying unique subtypes of spinal afferent nerve endings within the urinary bladder of mice. Issue 4 (15th December 2017) - Spencer, Nick J.; Greenheigh, Sarah; Kyloh, Melinda; Hibberd, Tim J.; Sharma, Harman; Grundy, Luke; Brierley, Stuart M.; Harrington, Andrea M.; Beckett, Elizabeth A.; Brookes, Simon J.; Zagorodnyuk, Vladimir P.
Abstract: Spinal afferent neurons are responsible for the transduction and transmission of noxious (painful) stimuli and innocuous stimuli that do not reach conscious sensations from visceral organs to the central nervous system. Although the location of the nerve cell bodies of spinal afferents is well known to reside in dorsal root ganglia (DRG), the morphology and location of peripheral nerve endings of spinal afferents that transduce sensory stimuli into action potentials is poorly understood. The individual nerve endings of spinal afferents that innervate the urinary bladder have never been unequivocally identified in any species. We used an anterograde tracing technique developed in our laboratory to selectively label only spinal afferents. Mice were anesthetized and unilateral injections of dextran‐amine made into lumbosacral DRGs (L5‐S2). Seven to nine days postsurgery, mice were euthanized, the urinary bladder removed, then fresh‐fixed and stained for immunoreactivity to calcitonin‐gene‐related‐peptide (CGRP). Four distinct morphological types of spinal afferent ending in the bladder were identified. Three types existed in the detrusor muscle and one major type in the sub‐urothelium and urothelium. Most nerve endings were located in detrusor muscle where the three types could be identified as having: "branching", "simple", or "complex" morphology. The majority of spinal afferent nerve endings were CGRP‐immunoreactive. Single spinal afferent axons bifurcated many times upon entering the bladder and developed varicosities along their axon terminal endings. We present the first morphological identification of spinal afferent nerve endings in the mammalian urinary bladder. Abstract : We present the first identification of spinal afferent nerve endings in the urinary bladder of a vertebrate mammal. In mice, four distinct morphological types of spinal afferent ending were identified. Three types existed in the detrusor muscle and one major type in the sub‐urothelium and urothelium.